Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1371/journal.pone.0004344
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus Response to Unsaturated Long Chain Free Fatty Acids: Survival Mechanisms and Virulence Implications

Abstract: Staphylococcus aureus is an important human commensal and opportunistic pathogen responsible for a wide range of infections. Long chain unsaturated free fatty acids represent a barrier to colonisation and infection by S. aureus and act as an antimicrobial component of the innate immune system where they are found on epithelial surfaces and in abscesses. Despite many contradictory reports, the precise anti-staphylococcal mode of action of free fatty acids remains undetermined. In this study, transcriptional (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(190 citation statements)
references
References 92 publications
8
181
0
1
Order By: Relevance
“…For enhanced local delivery of C2DA, we are currently investigating more biocompatible solvent systems in our laboratories. Some free fatty acids have been reported to have antimicrobial properties [13,14] and serve an important role in maintaining the microbial flora of the skin [29,43]. We demonstrated that C2DA inhibited bacterial growth at higher concentrations, but not at lower concentrations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For enhanced local delivery of C2DA, we are currently investigating more biocompatible solvent systems in our laboratories. Some free fatty acids have been reported to have antimicrobial properties [13,14] and serve an important role in maintaining the microbial flora of the skin [29,43]. We demonstrated that C2DA inhibited bacterial growth at higher concentrations, but not at lower concentrations.…”
Section: Discussionmentioning
confidence: 60%
“…This potential biofilm-preventative characteristic could make it useful as an adjunctive therapy for infection prevention. As in reports of several other medium-and long-chain fatty acids, studies have indicated that C2DA may also have growth inhibitory or bactericidal effects [14,29]. Further, since antibiotics have been less effective against biofilmassociated bacteria [40], C2DA could improve the efficacy of antibiotics in preventing or treating biofilm-associated infections.…”
Section: Introductionmentioning
confidence: 94%
“…The most potent antibacterial fatty acid in mice is 9-hexadecenoic acid, and in humans, its isomer 6-hexadecenoic acid [29]. In humans and mice, these two 16-carbon monounsaturated fatty acids block the growth of S. aureus in the skin [29][30][31]. It has been hypothesized that fatty acids act by destabilizing the lipid bilayers of the bacterial membrane and disrupting the membrane functions [32] due to a range of effects on cellular metabolism [33][34][35][36][37][38].…”
Section: Gc-ms Spectroscopymentioning
confidence: 99%
“…Both, S. aureus and S. saprophyticus express a cell wall associated surface protein, SsaF and SssF, respectively, that mediates resistance to the free fatty acid linoleic acid [85,86] . Furthermore, cell wall teichoic acids of S. aureus confer resistance to fatty acids from skin sebaceous glands [87] .…”
Section: Bacterial Mechanisms That Manipulate Host-derived Lipidsmentioning
confidence: 99%